Beneficial Impact of Homoeopathy in Slow Learners : A Pilot Study (Advancements in Homeopathic Research, 2022)
Academic performance constitutes an important bench mark in evaluating a child’s progress. Children with an IQ in range of 70 to 90 show difficulties in reading, comprehension, writing, vocabulary, grammar and mathematics, self esteem, social skills and deficient memory systems. Such children are said to be slow learners. The key management of slow learners lies in identification, diagnosis and prompt intervention; remedial and non remedial. The standard line of treatment for slow learners is open schools or vocational training .Homoeopathy literature has shown that the condition of slowness can be improved. A one year pilot study was conducted in three rural schools of Bangalore Rural and Ramnagar districts by the Dr. M. L. Dhawale Memorial Homoeopathic Institute, Bangalore to explore the role of Homoeopathic medicines in slow learners. Children under treatment have shown encouraging results in academic performance, especially reading comprehension and maths and improvement in self esteem and social skills. These encouraging results should be followed up through a carefully designed research study.
Keywords: slow learner; Homoeopathic therapy; non remedial interventions